Patent protection and foreign direct investment in Uganda's mining sector: a legal analysis of intellectual property as an investment incentive - Ntambi, Blair (Centre for Law and Society, 2026)
A conducive legal environment is a major attraction of foreign investment into a country. When potential investors are making investment decisions, they meticulously examine the laws and policies tailored by the host country to protect and manage their business assets, among other things. Examples of such laws include intellectual property laws that are categorised based on the specific intellectual rights associated with the technological innovations that the investor intends to employ in the host state. This thesis delves into Uganda's patent law ecosystem, specifically exploring how it can be strategically leveraged, by way of packaging it as an investment incentive, to attract greater foreign direct investment (FDI) in the country's mining sector. The country's mining sector is characterised by its intensive requirement for both capital and technological expertise. In so doing, the thesis makes the case that whereas tax incentives are often welcomed by foreign investors, those in technology-intensive sectors, such as mining, seek more comprehensive legal safeguards. Robust legal regimes, particularly patent regimes, are highly attractive as they shield investors' technological assets from misappropriation and infringement.